A new species of Laccobius Erichson, 1837 from China (Coleoptera: Hydrophilidae) - Jia, Fenglong; Song, Keqing; Gentili, Elio (Zootaxa, 2013)
A new species of the water scavenger beetle, Laccobius (Cyclolaccobius) martini sp. nov., is described from Shiwandashan, southern Guangxi Automomous Region, China. Digital photographs of several useful taxonomic features are provided. Additionally, the identification key to Laccobius (Cyclolaccobius) of China and neighbouring countries is updated to include this new species.